Challenges facing the African Union (AU) in the implementation of the Responsibility to Protect (R2P) : a case study of the 2010/2011 intervention in Côte d’Ivoire - Spies, Yolanda Kemp (University of Pretoria, 2015)
Mini-dissertation (MSecurity Studies)--University of Pretoria, 2015.